How protectionism harms workers under oligopoly - Jonas F. Rudsinske (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
I study welfare and distributional effects of import tariffs in a two-country asymmetric general oligopolistic equilibrium trade model. Tariffs have an anti-competitive effect that reduces labor demand because firms want to shorten supply. Unilaterally increasing the import tariff in absence of foreign retaliation raises domestic welfare at the foreign country's expense, but comes at the cost of favoring profit recipients as compared to workers, whose real wages fall. Only if initial symmetric tariffs are low, the tariff-increasing government could use its rising tariff revenue to neutralize the distributional effect or the negative effect on workers, an action the other country could never take because its tariff revenue declines. If supporting workers is the policy objective, tariffs do not appear to be a suitable tool under oligopoly and need to be accompanied by transfer payments or even profit taxation.
Keywords: F13; E25; F12; J23; L13; 330; Trade Policy; labor share; general oligopolistic equilibrium; labor demand; strategic trade